INTERNATIONALIZATION OF THE ECONOMY AS A KEY PREREQUISITE FOR THE ACTUALIZATION OF INTELLECTUAL LEADERSHIP - Kalenyuk, Iryna; Tsymbal, Liudmyla (Social Economics, 2020)
In the context of globalization, the issue of achieving high competitive positions and the factors that determine them is relevant. In this regard, the article explores the key prerequisites for the intellectualization of the economy, identifies the features and characteristics of the global space, one of the key factors of which is internationalization. The main subjects of intellectual leadership are identified, relationships and interdependencies are characterized. The tendencies of intellectualization and forms of their manifestation in the modern world are determined. In general, globalization effects are manifested in two planes: the characteristics of the international space and the transformational processes of interaction between the subjects of economic relations. In both planes, unidirectional processes continue - the formation of a single market, which can be expressed at the regional level as intellectual hubs. The globalization of intellectual activity is manifested through a change in the basic functions of higher education institutions and the principles of their functioning. In accordance with the new trends, the formation of a specific state policy aimed at expanding and expanding the boundaries of research is becoming relevant. The result of economic globalization can be considered the commercialization of scientific developments, including those carried out in higher education. It is determined that the state has the greatest influence on resource and environmental factors (creating conditions for the development of non-profit sector of economy, infrastructure, education, science, culture, guaranteeing access to them), while business significantly affects the achievement of intellectual activity (patent activity, formation flows of royalties and royalties, high-tech production, etc.) and their practical implementation. The development of the global market can be both a source of monopolies and a source of global innovation at the local level.